Makna Sukses di Masa Lanjut - Funi Rahmawati; Satih Saidiyah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
Being a successful elderly is the purpose of the development stage of late elderly. The aim of study was to determine the meaning of success reflected by the elderly couple. This study used a phenomenology approach through data collection methods were interview and observation. The results showed that the meaning of success was when they have the benefit of the previous enterprises and it shared with children and grandchildren. On the other hand, success also means the happiness of the family when the family is harmonious. As a couple, they capable in maintain mutually support each other and solving problem together. The factors have affecting in elderly success namely physical healthy, activities, psychological factors, social factors, and religiosity.